Genomic regions associated with bovine respiratory disease in pacific northwest Holstein cattle - Herrick, Allison L.; Kiser, Jennifer N.; White, Stephen N.; Neibergs, Holly L. (Frontiers in Veterinary Science, 2025)
IntroductionBovine respiratory disease (BRD) is the leading natural cause of death in cattle. It is a multifactorial disease comprised of bacterial and viral pathogens. To aid in the reduction of BRD morbidity and mortality and the selection of cattle with reduced susceptibility, the objectives of this study were to identify loci, gene sets, positional candidate and leading-edge genes associated with or enriched for BRD in pre-weaned and post-weaned Holstein calves.MethodsFrom a single dairy, 518 pre-weaned (0–60 days old) and 2,001 post-weaned (61–421 days old) Holstein heifers were treated for BRD and served as cases. All 3,655 pre-weaned healthy control calves remained in the herd for a minimum of 60 days, and 3,210 healthy post-weaned control calves remained in the herd for a minimum of 421 days. Loci associated (uncorrected p < 5 × 10−7) with BRD were identified using EMMAX with additive, dominant and recessive inheritance models. Positional candidate genes were identified within a haplotype of an associated SNP. A GSEA-SNP was performed to identify gene sets (NES ≥ 3) and leading-edge genes enriched for BRD.ResultsThere were four additive, six dominant, and three recessive loci associated (p < 5 × 10−7) with BRD in pre-weaned calves and 22 additive, 17 dominant, and 13 recessive loci associated with BRD in post-weaned calves. SNPs associated with pre-weaned BRD were within 26 positional candidate genes and 56 positional candidate genes in post-weaned calves. Heritability was estimated as 0.16 ± 0.02 for both groups. One gene set with 86 leading-edge genes was enriched (NES = 3.13) for the pre-weaned calves while 7 gene sets with 162 unique leading-edge genes were enriched (NES ≥ 3) in the post-weaned calves. The positional candidate genes, EBF1 and SPAG16, and the leading-edge gene COL4A3BP were shared between the pre-and post-weaned calves, which have functions related to inflammation and immune cell development. The identification of loci, gene sets, positional candidate and leading-edge genes associated and enriched for BRD in different ages of dairy calves provides a better understanding of the disease process and facilitates selection for animals more resistant to this complex disease.